Competence perspectives on managing interfirm interactions - Sanchez, Ron; Heene, Aimé (Advances in applied business strategy ;, 2005)
The competence-based perspective on strategy and management emerged in the 1990s as a new approach to developing strategy and management theory and practice. In the past decade, the focus on organizational competences - and the resources, capabilities, and processes that create competences - has provided a highly productive broad church for theory development, research, and practice in both strategic and general management. Authored by a multidisciplinary group of scholars and practitioners working within the competence perspective, the papers in this volume contribute to developing a better theoretical and practical understanding of interfirm interactions that significantly affect an organization's competences.The papers present both theoretical developments and empirical research based on a variety of case studies and other research in diverse industrial and geographical contexts. The papers in this volume develop three themes. Part I includes papers that address the key issues of managing activities in an organization's competence building and leveraging processes that span the boundaries of two organizations. The papers in Part II investigate the role of networks and strategic alliances in competence building and leveraging processes. Part III presents papers that investigate competitive interactions between firms in their competence leveraging activities.